MODEL PELURUHAN DAN REENTRI ORBIT SATELIT LEO - S.L. Manarung; Wlson Sinambela; Abd. Rachman (Jurnal Sains Dirgantara, 2007)
Based to the non-central Earth's gravity causing the sekuler variation on the semi mayor axis and ecentricity of the LEO's satellite the software of orbital decay has been developed. The input for the software is the height, eccentricity existed in TLE (Two Line Elemen table), anapproximated ballistic coefficient and the atmospheric density on virous solar activity. The software has been used to predict the time is to 10%, and the error will become smaller if the software is executed closed to reentry time such a week before satellite reentry. The softaware can be used to approximate the ballistic coefficient of a satellite.